2000
DOI: 10.1055/s-0037-1613839
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Change of Platelet Aggregability in Acute Hyperglycemia

Abstract: We examined the alteration of platelet aggregability in acute hyperglycemia during 75-gram oral glucose tolerance tests (OGTT). Twenty subjects underwent 75-gram OGTT and venous blood samples were obtained before (0 min), 60, 120 and 180 min postload. Platelet aggregability shown as the number of small platelet aggregates was measured with a novel laser-light scattering (LS) method. Platelet aggregability increased in parallel with both glucose and immunoreactive insulin (IRI) levels. The number of mean small … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 93 publications
(41 citation statements)
references
References 19 publications
2
38
0
1
Order By: Relevance
“…These findings may suggest that not only DM but also IGT is an important risk factor for CAD because oxidative stress in patients with IGT was as high as that in patients with DM. These findings are agreement with the previous reports that postprandial hyperglycemia is one of the risk factors for CAD through an increase in oxidative stress (6,15). Furthermore, it has been reported that hyperglycemia induces oxidative stress in an animal model and the level of thioredoxin is higher in patients with multiple coronary risk factors (16,17).…”
Section: Discussionsupporting
confidence: 93%
“…These findings may suggest that not only DM but also IGT is an important risk factor for CAD because oxidative stress in patients with IGT was as high as that in patients with DM. These findings are agreement with the previous reports that postprandial hyperglycemia is one of the risk factors for CAD through an increase in oxidative stress (6,15). Furthermore, it has been reported that hyperglycemia induces oxidative stress in an animal model and the level of thioredoxin is higher in patients with multiple coronary risk factors (16,17).…”
Section: Discussionsupporting
confidence: 93%
“…Several studies have demonstrated that acute hyperglycemia is a powerful predictor of mortality, larger infarct size and increased risk of cardiovascular complications in myocardial infarction patients regardless of the diabetic state [30][31][32][33][34][35]. For every 18-mg/ dL increase in glucose level, there is a 4% increase in mortality in nondiabetic patients presenting with myocardial infarction [36].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple physiological studies have shown that hyperglycemia has a direct detrimental effect on ischemic myocardium through several mechanisms, including oxidative stress, inflammation, apoptosis, endothelial dysfunction, hypercoagulation, and platelet aggregation. 14- 16 Brief episodes of antecedent myocardial ischemia have protective effects against subsequent prolonged ischemia, termed 'ischemic preconditioning'. Such effects are also generated by brief intermittent ischemia after the ischemic event (postconditioning) and observed even in remote organs (remote conditioning).…”
Section: Disclosuresmentioning
confidence: 99%